The Use of Animated Video Media to Improve Student Learning Outcomes on the Material of State Emblems and Pancasila Symbols at UPT SDN 043 Siunongunong Julu - Hotnida Manalu; Asrar Aspia Manurung; Ismail Saleh Nasution (EDUCATION JOURNAL OF INDONESIA, 2026)
This study aims to explore the impact of the application of animated video media in improving students' absorption of the National Emblem and Pancasila Symbols subject matter at UPT SD Negeri 043 Siunongunong Julu. This study involved 10 first-grade students of UPT SD Negeri 043 Siunongunong Julu, all of whom became research subjects. Using a quantitative approach, an experimental design was applied to compare two learning methods. In Cycle I, the control group received instruction using conventional methods, while in Cycle II, the experimental group was taught with animated video media. Data were collected through tests related to learning outcomes in the form of essay questions, which were then analyzed to see differences in learning outcomes. The results of the analysis showed that in Cycle I, the average score of students with the conventional method was 75.8, while in Cycle II, the use of animated video media produced an average score of 79.8, which was included in the medium category. The t-test revealed a significant difference between the two groups, where the experimental group showed better learning outcomes. Based on these findings, it is recommended that animated video media be used as an effective alternative in PKN learning, especially for the topic of State Emblems and Pancasila Symbols, in order to improve the quality of teaching and students' understanding.   Keyword: Pancasila symbols, animated videos, learning outcomes. conventional method was 75.8, while in Cycle II, the use of animated video media resulted in an averagescoreof 79.8, whichis included in themedium category. Thet tes trevealeda significant difference betweenthe twogroups,wheretheex perimental group showed better learning outcomes. Based on these findings, it is recommended that animated video media be used as an effective alternative in PKN learning, especially for the topics of National Emblems and Pancasila Symbols, in order to improve the quality of teaching and students' understanding.